Impact of Technological Innovations on Teaching-Learning Process in Technical Education:A Case Study - Patel, Anand S. (Journal of Engineering Education Transformations, 2007)
In the last decades of the twentieth century. World has seen remarkable growth in the field of Information Technology and Electronics&Communication. This offers number of challenges&opportunities to the various sectors. Education is one of them. In the light of Global Competitive Environment. Educational Institutes are considered as emerging pioneering service sector They are to put lots of effort to satisfy their valuable customers&to survive in the competitive environment. In this paper an attempt is made to understand the applications of latest technology in the field of Technical Education. The existing teaching methodology is to be reshaped by introduction of latest techniques like use of Multi - Media facilities. Intern et. Video Conferencing etc. This paper consists of five parts. The first part includes the basics of Teaching - Learning Process. The second part highlights the innovations in teaching aids and its application in Technical Education. The third part talks about the pros&corns of the application of teaching aids. The fourth part consists of a case study showing the impact of innovative teaching aids for the Diploma Students. The concluding part is a blend of remarks. suggestions&future of applications of innovative technology in Technical Education.